Developing the Traditional Game Engklek to Teach Arabic Grammar in Madrasah Tsanawiyah - Rohanda, Rohanda; Wildan Rinanda Komara; Syarah Salsabila; Ruly Syaeful Azhar; Qimanullah, Abdul Malik (Arabiyatuna: Jurnal Bahasa Arab, 2025)
Learning Arabic, particularly grammar, is often considered difficult and uninteresting by students because conventional methods tend to lack engaging learning activities. In line with the contextual learning theory, the use of traditional game-based media can enhance students’ motivation, engagement, and conceptual understanding. One form of local wisdom that has the potential to be adapted for learning is the traditional game Engklek. This study aimed to develop Engklek-based learning media as a tool for teaching Arabic grammar in an Islamic junior high school employing the Dick and Carey development model (analysis, design, development, implementation, and evaluation). The game design was tailored to grammar material, including exercises in taṣrīf lughawī (verb conjugation) and matching ḍamīr (pronouns) with their meanings. Validation by material and media experts indicated that the product was valid and suitable for use. A limited trial involving 21 students yielded an average feasibility score of 80.7%, with enthusiastic and participatory student responses. The findings demonstrate that the Engklek learning media effectively improved students’ understanding of Arabic grammar while contributing to the preservation of local culture. This study highlights the importance of integrating local wisdom into Arabic language learning innovations to create meaningful, contextual, and sustainable learning experiences.